Biogeography-based interference mitigation scheme for ofdma system in heterogeneous network - Hasan M.K.; Ismail A.F.; Abdalla A.-H.; Hashim W.; Islam S. (Science and Engineering Research Support Society, 2023)
Cochannel interference; Complex networks; Femtocell; Heterogeneous networks; Interference suppression; Mobile telecommunication systems; Signal interference; Signal to noise ratio; Spurious signal noise; Wave interference; Wireless telecommunication systems; Biogeography-based optimizations; Heterogeneous Network (HetNet); Interference mitigation; Macro cells; OFDMA; OFDMA systems; Shared channel; Signal to interference-noise ratios; Frequency division multiple access